(untitled) (Journal of Fiber Bioengineering and Informatics, 2012)
A series of self-reinforced, biocomposite fibers were successfully fabricated using Cellulose Nanowhiskers (CNWs) and cellulose matrix isolated from mulberry branch bark by wet spinning. The obtained CNWs have a diameter of about 20 nm and a length of 300-400 nm. The hybrid solutions containing less than 9 wt% CNWs were miscible according to the rheological curves. Specially, the synergistic interactions between fillers and matrix play a key role in reinforcing the composite fibers. The tensile strength and Young's modulus of composite fibers at 65% relative humidity increased from 172 to 571 MPa and 2.06 to 4.15 GPa with increasing CNWs content from 0 to 9 wt%.